A Systematic Review of Intrapartum Fetal Head Compression: What Is the Impact on the Fetal Brain? - Kent D. Heyborne (Thieme Medical Publishers, Inc., 2017)
Abstract Objective During labor the fetal head is subjected to pressure related to uterine contractions and maternal pushing. Here we systematically review what is known about fetal head compression and its effects on fetal intracranial pressure, oxygenation, blood flow and cerebral function, and the plausibility that it might cause isolated fetal brain injury. Study Design Systematic review of intrapartum fetal head compression and fetal brain injury in accordance with the MOOSE methodology. The PubMed database was searched using a combination of the terms "fetal," "head," "cranial," "extracranial," "pressure," and "compression." Additional references were obtained using multiple strategies. Results were evaluated, and relevant studies encompassing animal and human data using several approaches are summarized in this review. Results Studies support a significant increase in fetal extracranial pressure with contractions and pushing. However, available data do not support a concomitant significant relative increase in intracranial pressure, a reduction in cerebral circulation or oxygenation, or an impact on cerebral function. Conclusion A review of the literature indicates that fetal intracranial pressure is well protected from extracranial forces. Available data do not support intrapartum fetal extracranial pressure as a cause of fetal brain injury. Precis The fetal brain is relatively unaffected by intrapartum fetal head compression.